Organizational Culture, Career Development, and Job Satisfaction as Predictors of Nurses’ Turnover Intention in a Private Hospital - Sahara, Muhammad Anugrah; Subiyanto, Didik; Purnamarini , Tri Ratna (Amkop Management Accounting Review (AMAR), 2026)
Nurses’ turnover intention is a critical issue that can disrupt human resource stability and reduce the quality of hospital services. High workload, emotional pressure, and limited career development opportunities often encourage nurses to consider leaving their organization. This study aims to analyze the effect of organizational culture, career development, and job satisfaction on nurses’ turnover intention at RSU PKU Muhammadiyah Bantul. This research employed a quantitative approach using a survey method by distributing questionnaires to 69 nurses selected through simple random sampling. Data were analyzed using multiple linear regression with the assistance of IBM SPSS version 26. The results indicate that organizational culture does not have a significant effect on turnover intention partially, while career development and job satisfaction have a negative and significant effect on nurses' turnover intention. Simultaneously, organizational culture, career development, and job satisfaction significantly influence turnover intention. These findings suggest that improving career development opportunities and enhancing job satisfaction are essential factors in reducing nurses' intention to leave the organization. Therefore, hospitals are encouraged to implement human resource management policies that focus on structured career development programs and the improvement of nurses' job satisfaction to minimize turnover intention.